Dinamika Kontemporer Pengaruh Al-Qur'an, Hadits, dan Islam terhadap Bahasa Arab : Studi Kualitatif (International Forum of Researchers and Lecturers, 2025)
The Arabic language is closely linked to the Qur'an, Hadith, and Islamic teachings, which continue to evolve over time. This study aims to explore the contemporary dynamics of how these three aspects influence the development and usage of Arabic. A qualitative approach with a descriptive-analytical method is employed to examine lexical and grammatical changes, as well as language usage in various contexts, including education, preaching, and media. The findings indicate that the Qur'an and Hadith remain the primary references in shaping Arabic vocabulary and structure, while the development of Islam in the modern era also influences the adaptation and expansion of meanings across different fields. The study highlights the importance of a deep understanding of the relationship between language and religion in preserving the authenticity and relevance of Arabic in the era of globalization.